Early results of novel robotic surgery-assisted low anterior resection for rectal cancer and transvaginal specimen extraction by using Da Vinci XI: initial clinical experience - Çakır,Tuğrul (2021)
SUMMARY OBJECTIVE: The aim of this study is to evaluate the early results of robotic surgery-assisted low anterior resection for rectal cancer and transvaginal specimen extraction, regarding the operative time, operative and early postoperative complications, hospital stay, and pathological reports in a series of 10 patients. METHODS: From November 2016 to October 2019, case series study on patients diagnosed with RC was included in this study. All robotic-assisted low anterior resection of the rectum, vaginal removal of the specimen, colorectal anastomosis, and loop ileostomies were performed using the Da Vinci XI system. RESULTS: The mean age of patient was 64.8 (58–72) years. Low anterior resection was performed to seven patients, and very low anterior resection was performed to three patients. Total mesorectal excision of the rectum, transvaginal specimen extraction, transanal anastomoses, and protective ileostomy were performed in all 10 patients. The mean operative time was 275±30.50 min, and estimated blood loss was 50±10.50 mL. No patient required conversion to conventional surgery. Negative circumferential resection, proximal, and distal margins were accomplished negative. Mean number of lymph nodes harvested was 20±5.5. According to the pathological reports, all were adenocarcinoma. T1 stage was 80.0%, and T2 stage was 20.0%. Lymph node metastasis accounted for 80.0%. CONCLUSIONS: To our literature search, this is the first study reporting the early outcomes of the novel robotic surgery-assisted low anterior resection for rectal cancer and transvaginal specimen extraction by using the Da Vinci Xi system. It can be performed safely and successfully in selected patients by providing an excellent cosmetic body image, which may be important for women.